Osteogenic differentiation of dental pulp stem cells under the influence of three different materials. Issue 1 (December 2015) - Ajlan, Sumaiah; Ashri, Nahid; Aldahmash, Abdullah; Alnbaheen, May
Abstract Background Regeneration of periodontal tissues is a major goal of periodontal therapy. Dental pulp stem cells (DPSCs) show mesenchymal cell properties with the potential for dental tissue engineering. Enamel matrix derivative (EMD) and platelet-derived growth factor (PDGF) are examples of materials that act as signaling molecules to enhance periodontal regeneration. Mineral trioxide aggregate (MTA) has been proven to be biocompatible and appears to have some osteoconductive properties. The objective of this study was to evaluate the effects of EMD, MTA, and PDGF on DPSC osteogenic differentiation. Methods Human DPSCs were cultured in medium containing EMD, MTA, or PDGF. Control groups were also established. Evaluation of the achieved osteogenesis was carried out by computer analysis of alkaline phosphatase (ALP)-stained chambers, and spectrophotometric analysis of alizarin red S-stained mineralized nodules. Results EMD significantly increased the amounts of ALP expression and mineralization compared with all other groups (P < 0.05). Meanwhile, MTA gave variable results with slight increases in certain differentiation parameters, and PDGF showed no significant increase in the achieved differentiation. Conclusions EMD showed a very strong osteogenic ability compared with PDGF and MTA, and the present results provide support for its use in periodontal regeneration.